El Derecho a la vivienda: problemas, regulación y retos en el contexto peruano - Ortiz Sánchez, Iván (2023)
Is the Right to Adequate Housing recognized in the Peruvian Political Constitution of 1993? What has the Constitutional Court ruled regarding this Right? How may the Public Law help to overcome the challenges imposed by the need to guarantee the Right to Adequate Housing? This article tries to answer these questions by analyzing the regulation of the Right to Adequate Housing in international treaties and instruments applicable to our country, and the national regulation and jurisprudence. The last section will reflect on the challenges to the Right to Adequate Housing under the framework created by the National Housing and Urban Policy (2021) and the Act 31313, Sustainable Urban Development Act.